Proceedings of the 2nd Sari Mulia International Conference on Health and Sciences 2017 (SMICHS 2017) 2017
DOI: 10.2991/smichs-17.2017.74
|View full text |Cite
|
Sign up to set email alerts
|

Household Environment Factors Associated With Acute Respiratory Infection (Ari) Among Under-Five Children

Abstract: Objective: The purpose of this study was to find out the association of house environment with Acute Respiratory Infection (ARI) incidence in Pudi Village, North Kelumpang District, Kotabaru Regency. Method: This research was using a survey method with analytic cross-sectional study design. The Instrument was using observation list. Sample size about 90 houses and underfive children in Pudi village. They were taken by total sampling. The data were analyzed using Chi-square test. Results: Under-five children wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…This study found that there was no association between occupancy density with the incidence of ARI. This result is different from the several studies [11,45,46,48] that found a relationship between house density and the incidence of ARI in children under five. House conditions with an occupancy density of <9 m 2 /person only occurred in less than 9% of the observed houses.…”
Section: Physical House Conditioncontrasting
confidence: 99%
“…This study found that there was no association between occupancy density with the incidence of ARI. This result is different from the several studies [11,45,46,48] that found a relationship between house density and the incidence of ARI in children under five. House conditions with an occupancy density of <9 m 2 /person only occurred in less than 9% of the observed houses.…”
Section: Physical House Conditioncontrasting
confidence: 99%
“…An Indian study support this finding (11). As sleeping in the same house increase indoor air pollution, indoor smoke exposure (8,(12)(13)(14), and lack of ventilation (11,15). As a result, all these increase the development of pneumonia.…”
Section: Discussionmentioning
confidence: 77%
“…We found that the prevalence of ARIs was higher in respondents with indoor air pollution. Other studies in Papua, 13 Aceh, 9 Java, 10,11 , and Kalimantan 14,15 highlighted the dangers of overcrowded home and indoor air pollution, including smoking habits at home. The number of smokers was said to be proportional to the number of sufferers of health problems.…”
Section: Discussionmentioning
confidence: 99%